(x-9)(2x-1)=0

Simple and best practice solution for (x-9)(2x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-9)(2x-1)=0 equation:


Simplifying
(x + -9)(2x + -1) = 0

Reorder the terms:
(-9 + x)(2x + -1) = 0

Reorder the terms:
(-9 + x)(-1 + 2x) = 0

Multiply (-9 + x) * (-1 + 2x)
(-9(-1 + 2x) + x(-1 + 2x)) = 0
((-1 * -9 + 2x * -9) + x(-1 + 2x)) = 0
((9 + -18x) + x(-1 + 2x)) = 0
(9 + -18x + (-1 * x + 2x * x)) = 0
(9 + -18x + (-1x + 2x2)) = 0

Combine like terms: -18x + -1x = -19x
(9 + -19x + 2x2) = 0

Solving
9 + -19x + 2x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(1 + -2x)(9 + -1x) = 0

Subproblem 1

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Divide each side by '-2'. x = 0.5 Simplifying x = 0.5

Subproblem 2

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Solution

x = {0.5, 9}

See similar equations:

| 12+4x=132 | | x^2-10x+15=3x-15 | | 5u+v-11u+4v= | | g-27=2*45 | | 3n^2-10n-8=0 | | 3n^2-13n+4=0 | | 3n^2-13+4=0 | | 6x-27-50=7 | | 4xy(3yz)(-5xz)= | | 7*6=3t | | x^2+3=4x+35 | | 8x-16= | | 2x^2-12x+7=5 | | 0.45(6)+0.05x=0.15(24+x) | | 4X=6x^2 | | (2a-1)((4a)(4a)+2a+1)= | | 9(t-6)+6t=5(3t+2)-8 | | 0.25(10000)-0.04y=0.06(y+10000) | | -150=-5(-5b) | | -3y=6 | | 4(2y-1)-(2y)=6 | | x^2+9=8x | | (12y+5)(12y-5)= | | 2+2x+2=46 | | 5-5=16s-12s | | 3x(2x-1)=1 | | 42=-2x+6 | | (8p^3+3p^2-4)+(6p^3-3p+5)= | | 2(3x-8)=38 | | -16=-2a+7(5-7a) | | 6x-10=68 | | -77=7(-8x-3) |

Equations solver categories